Production, trade and livelihoods of cotton producers in Nigeria (2011)
The sustainable livelihood framework is applied to the context of cotton production and trade in Nigeria’s cotton belt with focus on small cotton farmers vulnerability to natural and environmental disasters; the effects of which policies and programmes were formulated to mitigate. The study aims at the application of multidisciplinary knowledge to the study of households and their livelihoods. In addition, the study helps to augment the pool of livelihoods research in Nigeria. With the aid of interviews and focus group discussions (FGDs), primary data were obtained from purposively selected communities in five northern states of Nigeria; namely Kano, Katsina, Kaduna, Zamfara and Jigawa in addition to secondary data on Nigeria’s cotton sector. The key finding of the study suggests that farmers are vulnerable to natural and environmental disasters as well as policy shocks to which some programmes and projects are targeted. The study also finds that institutional interventions to reduce vulnerabilities have been less successful in dealing with the restoration of small cotton farmers’ economic and social capital assets. Consequent upon the findings of the study, the adoption of sustainable livelihoods is germane for addressing cotton farmers ’ vulnerabilities in order to guarantee the success of poverty reduction strategies meant to help combat poverty for cotton producers.